À la recherche du temps maîtrisé - Marc Levêque (Temporalités)
The following contribution aims to identify and analyze, in the everyday experience of sports, an organizational and structural way of relating to time and then to characterize its possible effects on high-level practitioners. A voluntary scansion of time, backed up by the primacy of physiological processes, is accompanied by multiple and complex psychological effects, among which we will be considering:– a performance and efficiency that generate for the sportsman, as for the general public, but also for the world of business, a sense of perfect achievement. In fact, time management here is an ally, an instrument of progress and perfection,- the anxiety disorders and depressive episodes frequently generated in practitioners (objectivated by recent investigations), constantly on the alert to stick to the assignments and requirements of prescribed time,– a potential discrepancy between the input of objective time and the rhythms of psychological elaboration, for example in the case of failure, counter-performance, but also of unexpected successes… A potential desynchronization between experienced time, subjective and colored by the affects, on the one hand, planned and controlled time on the other, risks destabilizing the individual, temporal economy.